Surgical Outcomes of 23 Gauge Pars Plana Vitrectomy for Non Clearing Diabetic Vitreous Hemorrhage (Journal of Fatima Jinnah Medical University, 2024)
Background: Vitreous hemorrhage (VH) is one of the main causes of visual loss in patients with Diabetic Retinopathy. Initial management of VH is observation for 4-6 weeks. Non-clearing vitreous hemorrhage (NCVH) remains the most common indication for vitrectomy in such patients. The objective of the study was to investigate the surgical outcomes of 23-gauge vitrectomy with prior intravitreal bevacizumab for non-clearing diabetic vitreous hemorrhage.Patients and Methods: This was a prospective interventional case series conducted at Ophthalmology Department, Allied Hospital, Faisalabad from 1st January 2022 to 31st December 2022 (1 year). After obtaining IRB approval and informed consent, 50 patients with non-clearing vitreous hemorrhage (VH) were included in this study. Patients with any type of retinal detachment and previous retinal surgery were excluded. After initial detailed pre-op assessment, all patients underwent 3-port pars plana vitrectomy with 23G instrumentation using Binocular Indirect Operating Microscope (BIOM) system. Patients were followed up at one week, one month and three months to note visual acuity and any early or late post-operative complication. Data was analyzed by SPSS v. 25.0.Results: Out of 50 patients, 35 (70%) were female and 15 (30%) were male. Age ranged from 32 to 78 years with mean age of 55.5 years. Only 4 (8%) patients were type I diabetics. Mod pre-operative best corrected visual acuity was 3/60 and it improved to mode BCVA of 6/36 on Snellen chart. Complete resolution of VH occurred in 42 (84%) patients while 6 (12%) patients had recurrent VH. Most common postoperative complication noted was raised intraocular pressure in 19 (38%) patients.Conclusion: Our study suggested that 23-G vitrectomy is a safe option for patients with non-resolving diabetic vitreous hemorrhage. Mean BCVA improves after vitrectomy (depending on retinal status) and postoperative surgical complications also remain minimal.
Keywords: Diabetes Mellitus; Vitreous Hemorrhage; 23-guage Vitrectomy